Measurement of Autler-Townes and Mollow transitions in a strongly driven superconducting qubit. - Baur, M; Filipp, S; Bianchetti, R; Fink, J; Göppl, M; Steffen, L; Leek, P; Blais, A; Wallraff, A (2009)
We present spectroscopic measurements of the Autler-Townes doublet and the sidebands of the Mollow triplet in a driven superconducting qubit. The ground to first excited state transition of the qubit is strongly pumped while the resulting dressed qubit spectrum is probed with a weak tone. The corresponding transitions are detected using dispersive readout of the qubit coupled off resonantly to a microwave transmission line resonator. The observed frequencies of the Autler-Townes and Mollow spectral lines are in good agreement with a dispersive Jaynes-Cummings model taking into account higher excited qubit states and dispersive level shifts due to off-resonant drives.